Book Review of "Global Nuclear Developments: Insights from a Former IAEA Nuclear Inspector" by Pantelis F. Ikonomou - Arjun Banerjee (International Journal of Nuclear Security, 2021)
With a touching dedication to his grandchildren “in the hope that they will live in a world free of nuclear weapons,” a sentiment shared by numerous professionals working in the nuclear security and disarmament circuits, Pantelis F. Ikonomou sets the perfect stage for what is to follow in this excellent work. The author brings in his career-long expertise from important and sensitive programs, projects, and missions he has served in with the mother of all nuclear 3S (safety, safeguards, and security) organizations, the International Atomic Energy Agency (IAEA).